Illegal Control Over the Territory in International Law and the Status of Donbas Determination - Kresin, Oleksiy; Kresina, Iryna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
Total rejection of the aggression and territory occupation in the international law leads to their hybrid and concealed forms using gangs and mercenaries, proclaiming new “states” etc. These activities constitute serious threat to international security, can cause and already cause the fragmentation of states, anarchy, criminalization of politics, new forms of expansionism and so on. The authors of the article generalize the forms of illegal control over the territory in international law and their application considering the status of Donbas determination. International law for more than a century provides for the possibility of separate regulation of the sovereignty and legal rights of the state to the territory, on the one hand, and the implementation of the regime of illegal control over the territory – on the other. Authors argue that in the modern sense, primarily developed by doctrine and courts, illegal control over the territory can be considered as a legal regime, one of the forms of which is occupation, while others are defined as effective, overall, general, de facto control and related to undisclosed actions and informal means used by the aggressor states. This regime is characterized by the exercise of power over the territory by the will of a foreign state, and the forms of implementation of the regime differ depending on whether such a will is officially recognized or concealed. The transformation of international humanitarian law after the Second World War erased the boundaries between recognized and officially unrecognized occupation. But unlike occupation, the fact of which may be obvious, the fact of effective or other control over the territory requires the determination by judicial authorities. The qualification of illegal control by the Russian Federation of the Donbas in national and international law is ambiguous. The authors argue that the full recognition of the international armed conflict between Ukraine and Russia in Donbas, as well as Russia’s illegal control over latter should be expected in the process of consideration of a number of cases in the international judicial institutions.

Całkowite odrzucenie agresji i okupacji terytoriów w prawie międzynarodowym prowadzi do ich hybrydowych i ukrytych form wykorzystujących gangi i najemników, proklamowania nowych „państw” itp. Działania te stanowią poważne zagrożenie dla bezpieczeństwa międzynarodowego, mogą powodować i już powodują m.in. fragmentację państw, anarchię, kryminalizację polityki oraz nowe formy ekspansjonizmu. Autorzy artykułu uogólniają formy nielegalnej kontroli terytorium w prawie międzynarodowym i ich stosowanie z uwzględnieniem stanu determinacji Donbasu. Prawo międzynarodowe od ponad wieku przewiduje możliwość odrębnego uregulowania suwerenności i praw państwa do terytorium z jednej strony, a wprowadzenie reżimu nielegalnej kontroli nad terytorium – z drugiej. Autorzy argumentują, że we współczesnym rozumieniu wypracowanym przede wszystkim przez doktrynę i sądy, nielegalną kontrolę nad terytorium można uznać za reżim prawny, którego jedną z form jest okupacja, podczas gdy inne określa się jako skuteczne, całościowe, ogólne, de facto kontroli i związane z nieujawnionymi działaniami i nieformalnymi środkami stosowanymi przez państwo agresora. Reżim ten charakteryzuje się sprawowaniem władzy nad terytorium z woli obcego państwa, a formy realizacji reżimu różnią się w zależności od tego, czy taka wola jest oficjalnie uznana, czy zatajona. Transformacja międzynarodowego prawa humanitarnego po II wojnie światowej zatarła granice między uznaną i oficjalnie nieuznaną okupacją. Ale w przeciwieństwie do okupacji, której fakt może być oczywisty, fakt skutecznej lub innej kontroli nad terytorium wymaga ustalenia przez organy sądowe. Kwalifikacja nielegalnej kontroli Federacji Rosyjskiej nad Donbasem w prawie krajowym i międzynarodowym jest niejednoznaczna. Autorzy argumentują, że pełnego uznania międzynarodowego konfliktu zbrojnego między Ukrainą a Rosją w Donbasie, a także nielegalnej kontroli Rosji nad tym ostatnim, należy się spodziewać w procesie rozpatrywania szeregu spraw w międzynarodowych instytucjach sądowych.
Nielegalna kontrola terytorium w prawie międzynarodowym oraz ustalenie statusu Donbasu
Keywords: international law; international humanitarian law; illegal control over territory; occupation; aggression; effective control; de facto control; general control; prawo międzynarodowe; międzynarodowe prawo humanitarne; nielegalna kontrola terytorium; okupacja; agresja; skuteczna kontrola; de facto kontrola; kontrola ogólna